2013
DOI: 10.1016/j.infsof.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of systematic review process research in software engineering

Abstract: Context: Many researchers adopting systematic reviews (SRs) have also published papers discussing problems with the SR methodology and suggestions for improving it. Since guidelines for SRs in software engineering (SE) were last updated in 2007, we believe it is time to investigate whether the guidelines need to be amended in the light of recent research. Objective: To identify, evaluate and synthesize research published by software engineering researchers concerning their experiences of performing SRs and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
560
0
40

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 761 publications
(602 citation statements)
references
References 30 publications
2
560
0
40
Order By: Relevance
“…This paper shows a formal survey which combines well-known techniques such as SLR [23] and quality frameworks [7]. Thanks to this paper, organizations can formally plan, manage and perform a comparative on BPMSs and, later, analyze achieved results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper shows a formal survey which combines well-known techniques such as SLR [23] and quality frameworks [7]. Thanks to this paper, organizations can formally plan, manage and perform a comparative on BPMSs and, later, analyze achieved results.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account all these proposals, we have decided to follow the protocol defined by Kitchenham in our survey [ [21][22][23]] because it is considered one of the most acknowledged in software engineering. Our paper also takes into consideration Wohlin and Prikladnicki's [51] conclusions about SLRs in software engineering, since they consider that the search strategy is key to ensure a good starting point for the identification of studies and ultimately for the actual outcome of a particular study.…”
Section: Protocol Followed At This Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The main contribution of our paper is to establish a fair and practical discussion about the conduction of secondary studies in SE area. Several studies have reported experiences and lessons learned from researchers conducting secondary studies [3], [5], [6], [7]. However, these studies do not focus on the practical similarities and differences between secondary studies.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, SLR protocol adaptations to SE must be considered. Additionally, in a study from Kitchenham (2013) regarding using SLRs in SE, she concludes that the three most significant problems are: (i) digital libraries are not well suited to complex automated searches, (ii) the time and effort needed for SLRs and (iii) the quality assessment of papers based on different research methods.…”
Section: Introductionmentioning
confidence: 99%